Do Firms Benefit from Concentrating their Borrowing? Evidence from the Great Recession - Gobbi, Giorgio; Sette, Enrico (Review of Finance, 2014)
Abstract We investigate whether the extent to which firms concentrate their borrowing from banks mitigates the credit contraction that followed the default of Lehman. Using micro data from a large sample of Italian firms, we show that firms borrowing from fewer banks and those with more concentrated borrowing suffer on average a smaller contraction in bank credit and have a lower probability of being credit-rationed. The results hold controlling for several firm-level characteristics and for the possible endogeneity of the measures of concentration of borrowing.